Evolution of food insecurity in Sudan during the ongoing conflict - Kirui, Oliver K.; Siddig, Khalid; Fisher, Monica; Abushama, Hala; Ahmed, Mosab O. M.; Raouf, Mariam; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2024)
Sudan's food security landscape has been dramatically impacted by the ongoing conflict between the Sudanese Armed Forces (SAF) and the Rapid Support Forces (RSF), which began in April 2023. The conflict has exacerbated an already precarious situation for the country, characterized by macroeconomic instability, climate shocks, and persistent discord and tension. This policy note analyzes the evolution of food insecurity in Sudan during the conflict, drawing from analysis of four nationwide surveys conducted before and during the conflict, namely the 2022 Sudan Labor Market Panel Survey (SLMPS),1 the 2023/24 Sudan Rural Household Survey,2 the 2024 Sudan Urban Survey,3 and the recently completed 2024 Rural Household Survey. The findings highlight significant deterioration in food security across rural and urban areas of Sudan. Based on insights from these surveys, policy recommendations are offered to address food insecurity in the context of the conflict in Sudan. Before the outbreak of the conflict in 2023, Sudan was already facing significant food insecurity challenges. The 2022 SLMPS, a nationwide survey conducted in person, revealed that approximately 49 percent of Sudanese households were food secure. Factors such as high inflation, climate-related shocks, and underinvestment in agriculture have led to many households facing problems accessing sufficient healthy food, adversely affecting their food consumption. The reliance of Sudan on imports for a significant share of food consumption, coupled with a devaluating Sudanese Pound and rising inflation, strained household purchasing power, further limiting access to essential foodstuffs. Food insecurity was uneven across the country. Rural areas, where consumption of own agricultural production is essential for household food security, had higher food insecurity than urban areas. Some regions were particularly vulnerable to food insecurity, including the Darfur and Kordofan regions and Blue Nile states. Localized conflicts in these areas disrupted agricultural activities and displaced communities even before broader-scale fighting between SAF and RSF began.